Chapter Treblinskij ad di V. Grossman nell'Europa dell'immediato dopoguerra (1945-1947) - BOSCHIERO, Manuel (Biblioteca di Studi Slavistici, 2019)
The literary essay Treblinskij ad (The Hell of Treblinka), written by Vasilij Grossman and first published in the journal Znamja in 1944, circulated widely at the end of World War II, with editions appearing in several different languages. This article examines how Treblinskij ad spread across Europe and the United States during the Nuremberg Trials. We focus on the English, French, and German translations of the text that appeared between 1945 and 1947, and compare these translations with the versions of Grossman's essay that were published in Russia.